The Role of Students’ Mother Tongue in EFL Classes - Gautam, Pitamber (English Language Teaching Perspectives, 2025)
The use of the mother tongue in learning a foreign language has long been a subject of ongoing debate, particularly in multilingual contexts like Nepal. This study aimed to explore the role of students’ mother tongue in EFL instruction through the lens of five key themes as for pedagogical significance; psychological and emotional impact; the use of a blended teaching approach; students’ perspectives towards mother tongue and respecting intra-cultural properties by fostering intercultural coexistence between native and foreign languages. Employing a qualitative phenomenological research design, data were collected through semi-structured interviews and non-participant classroom observations. The results revealed that the strategic use of the students’ mother tongue reduces language anxiety, boosts comprehension and builds confidence especially for the students with limited English exposure. Translanguaging proved to be an effective teaching tool for them to enhance engagement and understanding. Attitudes of teachers and students towards using their mother tongue were found much varied as those from community schools favoured its inclusion for better comprehension and performance while the ones from the institutional schools advocated to minimize it to promote an optimum English exposure and learning environment. This research underscores the significance of maintaining a balanced context–sensitive approach in EFL classes. It orients the concerned stakeholders to focus on teacher training, curriculum design and resource management apt to the native ground realities. The findings offer valuable insights for educators, policy makers and curriculum designers to create an inclusive and effective EFL learning environment opening a wide horizon for further research on this long stranded contentious issue.